Grupo pequeño de personas. - Universidad Estatal a Distancia (San José, Costa Rica : UNED)
Aparecen Chester Zelaya Goodman, Johana Meza Vargas y Carlos Hernández
Colección Fototeca UNED
Keywords: UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA; Zelaya Goodman, Chester, Rector UNED -- 1981-1986; Meza Vargas, Johanna; Hernández Orozco, Carlos